Wolbachia stimulates immune gene expression and inhibits plasmodium development in Anopheles gambiae. - Zakaria Kambris; Andrew M Blagborough; Sofia B Pinto; Marcus S C Blagrove; H Charles J Godfray; Robert E Sinden; Steven P Sinkins (PLoS Pathogens)
The over-replicating wMelPop strain of the endosymbiont Wolbachia pipientis has recently been shown to be capable of inducing immune upregulation and inhibition of pathogen transmission in Aedes aegypti mosquitoes. In order to examine whether comparable effects would be seen in the malaria vector Anopheles gambiae, transient somatic infections of wMelPop were created by intrathoracic inoculation. Upregulation of six selected immune genes was observed compared to controls, at least two of which (LRIM1 and TEP1) influence the development of malaria parasites. A stably infected An. gambiae cell line also showed increased expression of malaria-related immune genes. Highly significant reductions in Plasmodium infection intensity were observed in the wMelPop-infected cohort, and using gene knockdown, evidence for the role of TEP1 in this phenotype was obtained. Comparing the levels of upregulation in somatic and stably inherited wMelPop infections in Ae. aegypti revealed that levels of upregulation were lower in the somatic infections than in the stably transinfected line; inhibition of development of Brugia filarial nematodes was nevertheless observed in the somatic wMelPop infected females. Thus we consider that the effects observed in An. gambiae are also likely to be more pronounced if stably inherited wMelPop transinfections can be created, and that somatic infections of Wolbachia provide a useful model for examining effects on pathogen development or dissemination. The data are discussed with respect to the comparative effects on malaria vectorial capacity of life shortening and direct inhibition of Plasmodium development that can be produced by Wolbachia.